Physiological quality and imbibitions of soybean seeds with contrasting coats - Carlos André Bahry; Anelise Tessari Perboni; Maicon Nardino; Paulo Dejalma Zimmer (Revista Ciência Agronômica)
ABSTRACT The attributes that confer seed quality can largely be considered dependent on the coat. The aim of this study was to evaluate the quality and hydration pattern of the seeds of four contrasting soybean genotypes for the coats characteristics; BMX Potência RR and CD 202 with yellow coats and IAC and TP with black coats. The first stage of the study consisted of seed multiplication in the 2012/2013 harvest. After storage for five months at a temperature of 17 ºC and a relative humidity of 50%, the seeds were subjected to the following tests: germination, first count and seedling height, with and without immersion of the seeds, emergence in soil, emergence speed and germination index; electrical conductivity; thousand weight seeds and imbibitions of seeds. The design was completely randomized, with five replicates. The data was subjected to variance analysis and the means compared using the Tukey test at a 5% level of probability. Regression analysis was used for the seeds imbibitions test. Genotypes with black coats (especially IAC) presented better physiological quality in relation to genotypes with yellow coats. The latter had greater thousand weight seeds. BMX Potência RR presented greater hydration than the other genotypes in the first hours of imbibitions and TP, the least. Genotypes with black coats emitted a radicle faster than the yellow coats genotypes.